Development of Biofuels in China : Technologies, Economics and Policies - Shiyan, Chang (World Bank, Washington, DC, 2013)
China promulgated the Medium and Long-Term Development Plan for Renewable Energy in 2007, which included targets of 2010 and 2020 for various renewable energy technologies including biofuels. The 2010 biofuel targets were met and even surpassed except for non-grain fuel ethanol; however, there is debate on whether and how the country will be able to meet the 2020 biofuels target. This paper provides a resource and technological assessment of biofuel feedstocks, compares biofuel production costs from various feddstocks and technologies, and evaluates policies introduced in the country for the development of biofuels. The paper also presents the projections on the production of biofuels under various policy scenarios. The study shows that China can potentially satisfy its non-grain fuel ethanol target by 2020 from the technology perspective. But it will probably fall far short of this target without additional fiscal incentives as production costs of non-grain feedstock based biofuels are expected to remain relatively high. By contrast, the 2020 target of biodiesel production has a high probability of being achieved because the target itself is relatively small. With additional support policies, it could develop even further.